Akuntansi Berbasis Blockchain: Memperkuat Transparansi, Akuntabilitas, dan Keamanan Sistem Keuangan - Enny Istanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The development of blockchain technology has brought significant changes in various sectors, including in the field of accountingThis research uses a qualitative approach with literature study and case analysis methods. Through a comprehensive review of related theories, journals, and case studies, the results of the study show that the implementation of blockchain technology has presented a fundamental transformation in modern accounting practices. Research shows a significant increase in financial system transparency after blockchain implementation. The implementation of blockchain has had a significant impact on strengthening the accountability of the financial system. The results of the study show substantial strengthening in the security aspect of the financial system through the implementation of blockchain. Based on the results of a comprehensive analysis of the application of blockchain technology in accounting practices, it can be concluded that this innovation provides a fundamental transformation in financial recording and reporting systems. In terms of accountability, the implementation of blockchain in accounting systems has presented a new paradigm in financial accountability. The security of the financial system has been significantly improved through the application of advanced cryptography in blockchain architecture. The integration of artificial intelligence with blockchain-based accounting systems further strengthens analytical and predictive capabilities in financial management.